OPPOSITION IN KAZAKHSTAN: NAGGING PROBLEMS - KARMAZINA, Lydia (CENTRAL ASIA AND THE CAUCASUS, 2009)
Today there are ten political parties in Kazakhstan but only one of them—the People’s Democratic Nur Otan Party—supports the government. The rest are regarded as the opposition.The Communist Party of Kazakhstan (CPK), the Communist People’s Party of Kazakhstan (CPPK), the Azat Democratic Party of Kazakhstan, and the National Social-Democratic Party of Kazakhstan (NSDPK) can be described as the active opposition. The camp of the moderate opposition is made up of the Ak Zhol Democratic Party of Kazakhstan, the Adilet Democratic Party, the Party of the Patriots of Kazakhstan (PPK), the Kazakhstan Auyl SocialDemocratic Party, and the Rukhaniat Party.The parties’ relations with the government, their political views, their actions, and the tone of their statements divide the parties into active and moderate.The moderate is critical yet, on the whole, constructive when it comes to a dialog with the other parties and the government; the active are mostly driven by the idea consolidating the opposition bloc into a united front to stand opposed to the ruling elite.Heated polemics about whether or not the opposition in Kazakhstan meets the standards political science has established in the West have been going on for some time now. The analytical and expert communities have more or less agreed that the answer is “No.”1This approach is based on the critical/loyal attitude toward the government or, rather, toward the president. Some people mistake oppositional sentiments for an anti-system stance.Political science claims that a party becomes oppositional when either it has lost an election or fails to achieve a parliamentary majority thus standing no chance of acquiring a place in the cabinet. This means that the degree of involvement in executive state power is the main criterion.Several parties may win an election and form a coalition government while opposition parties might acquire seats in the parliament to form a parliamentary opposition.